Chemiresistive hydrogen sensors using a Pd-Ni nanocatalyst and a TiOx/PTFE humidity passivation - Duy, Le Thai; Yeasmin, Rubaya; Han, Seung Ik; Iqbal, Shahid; Park, Chiwan; Seo, Hyungtak (Sensors and Actuators B: Chemical, 2023)
Hydrogen sensors are important not only in producing, storing, and handling hydrogen fuel but also in using hydrogen-powered devices. However, there are various challenges for practical use and commercialization of gas sensors such as (i) the cost reduction of materials for mass production, (ii) the sensitivity of the sensors towards a wide concentration range of analyte gas, and (iii) the stability of the sensors, especially in high humidity levels. For the first two objectives, our miniaturized resistive sensor based on a multilayered Pd-Ni nanocatalyst is developed. Our Pd-Ni sensors possessed excellent hydrogen sensitivity from 20 ppm to 100 % at room temperature. To solve the problem of humidity interference, polytetrafluoroethylene (PTFE) and titanate (TiOx) are used for passivating the sensors. With passivation, our sensors can operate well under high relative humidity conditions of up to 85 % RH at operating temperatures ≤ 80 °C. More importantly, the passivated Pd-Ni sensors are produced using dry methods (e-beam evaporation and sputtering), which are highly applicable in industrial-scale manufacturing.
Keywords: Bimetallics; Commercialisation; Costs reduction; Gas-sensors; Humidity passivation; Hydrogen sensor; Mass production; Nano-catalyst; Powered devices; Practical use; Bimetallic; Humidity passivation; Hydrogen sensor; Nanocatalyst; PTFE